The meaning of the independence of Central America in its bicentennial 1821- 2021 (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The independence of Central America as it has been expressed in these 200 years had to do without any place with external and internal phenomena, in the first case the independence of the 13 North American colonies in 1776, the late 18th century illustration, the French Revolution In 1789, the invasion of Napoleon Bonaparte in 1808 and the Bourbon Reforms caused the greatest vacuum in the history of royal power, the removal of Ferdinand VII was the necessary soup for the Spanish colonies in America and the Caribbean to cause the stampede of royal officials and that by effect they would self-proclaim independence for all the vast territories previously ruled with the royal judo.
Keywords: history; bicentennial; independence